Bibliometric analysis of scientific papers on extracellular vesicles in kidney disease published between 1999 and 2022 - Hun, Marady; Wen, Huai; Han, Phanna; Vun, Tharith; Zhao, Mingyi; He, Qingnan (Frontiers in Cell and Developmental Biology, 2023)
Background: In recent years, there has been an increasing interest in using extracellular vesicles (EVs) as potential therapeutic agents or natural drug delivery systems in kidney-related diseases. However, a detailed and targeted report on the current condition of extracellular vesicle research in kidney-related diseases is lacking. Therefore, this prospective study was designed to investigate the use of bibliometric analysis to comprehensively overview the current state of research and frontier trends on extracellular vesicle research in kidney-related diseases using visualization tools. Methods: The Web of Science Core Collection (WoSCC) database was searched to identify publications related to extracellular vesicle research in kidney-related diseases since 1999. Citespace, Microsoft Excel 2019, VOSviewer software, the R Bibliometrix Package, and an online platform were used to analyze related research trends to stratify the publication data and collaborations. Results: From 1 January 1999 to 26 June 2022, a total of 1,122 EV-related articles and reviews were published, and 6,486 authors from 1,432 institutions in 63 countries or regions investigated the role of extracellular vesicles in kidney-related diseases. We found that the number of articles on extracellular vesicles in kidney-related diseases increased every year. Dozens of publications were from China and the United States. China had the most number of related publications, in which the Southeast University (China) was the most active institution in all EV-related fields. Liu Bi-cheng published the most papers on extracellular vesicles, while Clotilde Théry had the most number of co-citations. Most papers were published by The International Journal of Molecular Sciences, while Kidney International was the most co-cited journal for extracellular vesicles. We found that exosome-related keywords included exosome, exosm, expression, extracellular vesicle, microRNA, microvesicle, and liquid biopsy, while disease- and pathological-related keywords included biomarker, microRNA, apoptosis, mechanism, systemic lupus erythematosus, EGFR, acute kidney injury, and chronic kidney disease. Acute kidney disease (AKI), CKD, SLE, exosome, liquid biopsy, and extracellular vesicle were the hotspot in extracellular vesicle and kidney-related diseases research. Conclusion: The field of extracellular vesicles in kidney-related disease research is rapidly growing, and its domain is likely to expand in the next decade. The findings from this comprehensive analysis of extracellular vesicles in kidney-related disease research could help investigators to set new diagnostic, therapeutic, and prognostic ideas or methods in kidney-related diseases.